(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
Active learner engagement, contextual understanding, and independent learning strategies are emphasized as crucial for effective vocabulary teaching. This article provides detailed insights into the principles of teaching and learning lexis. Vocabulary development is shown to improve overall communicative competence. Each principle, including contextualization, active participation, recycling, integration of form and meaning, learner autonomy, and personalization, is analyzed as a key factor for successful lexical instruction. The article is based on methodological analysis and a review of relevant literature.